2019
DOI: 10.1371/journal.pone.0222104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the application of irrigated water-soluble calcium fertilizer on wine grape properties

Abstract: The eastern foot of Helan mountain is a famous production area of high-end wine grapes in China. Excessive application of NPK fertilizer induced deficiency in trace elements, such as calcium, and seriously affected the properties of wine grapes. A vineyard in the eastern foot of Helan mountain was selected to investigate the influence of five different concentration treatments of 15 (T 1 ), 30 (T 2 ), 45 (T 3 ), 60 (T 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Therefore, calcium supplementation is an important measure to improve fruit quality [28] . This study shows that foliar application of calcium sugar alcohols can increase the particle size, hundred-grain weight, and yield of wine grapes, which is similar to the results of Wang et al [8] The increase in diameter, hundred-grain weight, and yield reached 2.66%-21.97%, 2.59%-63.08%, and 10.25%-30.72%, respectively. Zhang et al [26] concluded that the application of calcium fertilizer increases the soluble solids in wine grapes and improves the sugar-acid ratio.…”
Section: Effects Of Calcium Application On the Yield And Quality Of W...supporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, calcium supplementation is an important measure to improve fruit quality [28] . This study shows that foliar application of calcium sugar alcohols can increase the particle size, hundred-grain weight, and yield of wine grapes, which is similar to the results of Wang et al [8] The increase in diameter, hundred-grain weight, and yield reached 2.66%-21.97%, 2.59%-63.08%, and 10.25%-30.72%, respectively. Zhang et al [26] concluded that the application of calcium fertilizer increases the soluble solids in wine grapes and improves the sugar-acid ratio.…”
Section: Effects Of Calcium Application On the Yield And Quality Of W...supporting
confidence: 90%
“…Because plant roots absorb nutrients from the soil and transport them to other organs, it has been found that supplementing calcium fertilizers by irrigation or soil fertilization has achieved good results on a variety of fruit trees. Wang et al [8] showed that the titratable acidity, anthocyanin, and total phenolic content of grape berries were significantly increased after drip irrigation with Ca(NO 3 ) 2 •4H 2 O at a concentration of 3.0 kg/hm 2 . At this dose, it effectively prevented grape cracking, inhibited cell wall disintegration, promoted cell wall strengthening [9] , and prolonged the effective storage time of grapes after harvesting [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The content of soluble solids was determined by hand-held sugar meter; the content of reducing sugar was determined by 3,5-dinitrosalicylic acid method; the content of titratable acid was determined by standard 0.1 mol/L NaOH (end point pH 8.2) (Jin et al, 2016;Ma et al, 2019;Wang et al, 2019).…”
Section: Determination Of Cabernet Sauvignon Fruit Qualitymentioning
confidence: 99%
“…Although grapevine growth requires microelements in small amounts, these nutrients may significantly affect grape properties [26]. It was informed that calcium plays an important role in cell division, as well as in the growth and development of fruit trees [27].…”
Section: Plos Onementioning
confidence: 99%
“…According to Couto et al [25], boron application controlled M. incognita population. Another important plant nutrient is calcium, which is considered a structural component of plant cell walls [26] and the development and structural integrity of plant membranes [27]. It was reported that the shortage of calcium in the soil affects plant structures and make plants less resistant to nematode infections [28].…”
Section: Introductionmentioning
confidence: 99%